P129 Autologous blood patch pleurodesis – a UK multi-centre retrospective case series. (11th November 2022) - Shakir, S; Choo-Kang, B; Conroy, K; Ross, C; Thorley, R; Walker, S; Aujayeb, A
Abstract : Introduction: Treatment of persistent air leak (PAL) due to pneumothorax is challenging. Autologous blood patch pleurodesis (ABPP) is a treatment option. Previous evidence is reliant on single centre series, underpowered trials and are mostly described in air leaks post cardiothoracic intervention. There is no United Kingdom (UK) wide data. Methods: Members of the UK Pleural Society were surveyed for patients who underwent ABPP. The results of the survey will be presented at the European Society (16 respondents from 333 members, 12 had performed the procedure, 6 could submit data). Basic demographics, intervention and clinical details of patients were then collected. Results: Data for 12 patients that received ABPP between 2014 and 2022 in 6 respiratory centres was assessed. 11 patients had secondary spontaneous pneumothoraces (SSP) and 1 a pneumothorax followed an oesophagectomy. The underlying pathology of pneumothorax is shown in table 1 . Median PAL time before ABPP was 17.5 days (range 6–43). 50–100 mls of blood was used for ABPP. 5 Patients had 2 attempts at ABPP. PAL resolved after ABPP in 6 patients (50%), 1 of whom received 2 attempts at ABPP. Median time to leak cessation was 5 days (1–7). Only 2 patients had pleural apposition prior to ABPP attempts and only one of those had cessation of PAL post ABPP. Where ABPP was unsuccessful, 2 patients received endobronchial valves which resolved PAL and 1 underwent thoracoscopic surgery with a wedge resection which achieved PAL resolution. 1 achieved lung apposition following ABPP allowing talc pleurodesis resulting in cessation of PAL. 5 patients were diagnosed with hospital acquired pneumonia following ABPP with 3 of those patients dying during their index episode of care. Conclusion: This is the 1st UK wide retrospective case series of ABPP of 'medical' patients with pneumothorax. ABPP is seldom used but can prove effective although mortality is high in this patient group. Lung apposition is not required prior to ABPP. Much larger numbers and robust clinical data is required- an application has been made to the European Respiratory Society to incorporate ABPP within the International Collaborative Effusion (ICE) database (https://erj.ersjournals.com/content/53/5/1900591 ).